Pengaruh Perputaran Kas, Perputaran Piutang Dan Perputaran Modal Kerja Terhadap Rentabilitas Pada PT Wijaya Karya - Edy Firmansyah; Anto Tulim; Dina Hastalona; Desliani Zalukhu (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
Economic rentability is the achievement achieved by a company expressed in percentage terms, after being compared between the results obtained with the capital used. In addition to increasing economic rentability, there are still other factors that are no less important to pay attention to companies in assessing the level of efficiency of the company, among others, judging from the rate of cash turnover, receivable turnover and working capital turnover. This research aims to find out the effect of cash turnover, receivable turnover and working capital turnover on economic rentability both partially and simultaneously on PT. Wijaya Karya (Persero) Tbk. The research method used by researchers is descriptive quantitative by using data from financial statements of PT. Wijaya Karya (Persero) Tbk. Based on the results of research conducted it can be known that partially variable cash turnover and working capital turnover do not have a significant effect on economic rentability, and partial receivable turnover has a significant effect on economic rentability. Simultaneously variable cash turnover, receivable turnover and working capital turnover have a significant effect on economic rentability.